2013
DOI: 10.1007/s10517-013-2107-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Contractile Activity of Rabbit Colon under Stress Conditions and during Post-Stress Period before and after Blockade of Muscarinic and Nicotinic Cholinergic Receptors

Abstract: Psychogenic stress in rabbits induced by fixation of the animal to a frame was accompanied by an increase in contractile activity of the initial portion of the distal colon, which was abolished by blockade of muscarinic and nicotinic cholinergic receptors. Increased contractile activity of the colon was due to centrogenic stimulation of preganglionic neurons of the parasympathetic nervous system followed by the involvement of the effector cholinergic neurons of the enteric nervous system into excitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…JPET Fast Forward. Published on June 15, 2021 as DOI: 10.1124/jpet.121.000587 at ASPET Journals on June 20, 2021 jpet.aspetjournals.org Downloaded from (Ovsiannikov and Berezina 2013;Chen et al 2018). It has been reported that after II/R injury, the content of ChAT, a key enzyme in the synthesis of ACh, ACh as well as the expression level of M3 protein decreased (Paulino et al 2011;Palombit et al 2013), which may be one of the main reasons for the decrease of intestinal smooth muscle tension after II/R injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…JPET Fast Forward. Published on June 15, 2021 as DOI: 10.1124/jpet.121.000587 at ASPET Journals on June 20, 2021 jpet.aspetjournals.org Downloaded from (Ovsiannikov and Berezina 2013;Chen et al 2018). It has been reported that after II/R injury, the content of ChAT, a key enzyme in the synthesis of ACh, ACh as well as the expression level of M3 protein decreased (Paulino et al 2011;Palombit et al 2013), which may be one of the main reasons for the decrease of intestinal smooth muscle tension after II/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal autonomic contraction tension is a direct index to evaluate the intestinal function (Ovsiannikov & Berezina 2013). In this study, the autonomic contraction of jejunum rings was observed after the jejunum rings in the isolated tissue perfusion system was stable.…”
Section: Effects Of Anwulignan On the Jejunal Tension In Vitromentioning
confidence: 94%